(untitled) (Research, Society and Development, 2024)
Introduction: The appropriate attendance to the prenatal should provide the reception to the woman respecting the emotional and physiologic changes inherent to the gestation, considering your doubts, fears and anguishes related to this moment of your life. Being like this, it’s necessary also that that accompaniment can be monitored through indicators that it makes possible to evaluate the adaptation of the rendered service. This study descriptive, documental, traverse and analytic with quantitative approach aimed at to. Evaluate: The Accompaniment to the Prenatal in the Sanitary District II of the municipality of Campina Grande-PB. Resulted e discuses: Verified that 99,71% of the registered pregnant women were accompanied by the Community Agent of Health; 97,70% were up-to-date with the vaccines; 90,83 were up-to-date with prenatal consultation. With relationship to the begining of the prenatal in the first quarter the results they showed a percentile of 76,79%; evaluating the pregnant women distribution accompanied by age group the obtained results they showed that 58% of the studied pregnant women were smaller of 20 years. Final Considerations: Before the exposed, he/she was considered through this study that the accompaniment to the prenatal was shown quite satisfactory, though it is done necessary that the attendance to the prenatal is organized in a continuous and systematic way with actions assistences and educationals through a team qualified multiprofissional, that guaranteeing that woman’s precocious reception, appropriate accompaniment and humanized, parturition and the safe birth.